The Role of Cardiac Magnetic Resonance in the Evaluation of Patients Presenting with Suspected or Confirmed Acute Coronary Syndrome - Loren P. Budge; Michael Salerno (Cardiology Research and Practice)
Cardiac magnetic resonance imaging (CMR) has an important emerging role in the evaluation and management of patients who present with symptoms concerning for acute coronary syndrome (ACS). This paper discusses the role of CMR in the emergency department setting, where CMR can aid in the early and accurate diagnosis of non-ST elevation ACS in low and intermediate risk patients. For those with confirmed myocardial infarction (MI), CMR provides comprehensive prognostic information and can readily diagnose structural complications related to MI. Furthermore, the pattern of late gadolinium enhancement (LGE) seen on CMR can help determine the etiology of cardiac injury in the subset of patients presenting with ACS who do not have obstructive coronary artery disease by angiography.